Impact Analysis Of Current Import Export Policy Covid 19 Pandemic On Old Iron MSMEs (Analysis Of The Impact Of Export-Import Policy During The Covid-19 Pandemic On MSMES Of Sold Iron) - Ratna Ekasari; Mukti Ali; Sri Utami (JURNAL EKBIS, 2022)
The background of the eczema policy during the pandemic based on PP No. 21 of 2020 concerning Large-Scale Social Restrictions has had a detrimental impact on the community. This study aims to determine the level of losses experienced by Old Iron SMEs. Primary data were collected by interview, observation and documentation methods. The Impact of the Covid-19 Pandemic ExportImport Policy on Scrap Metal SMEs in maintaining businesses affected by the COVID-19 pandemic in the Sumberwono Bangsal area, Mojokerto Regency. In this study, researchers obtained data using interview, observation and documentation methods from this study, it is known that the Old Iron MSME actors experienced a 50% - 60% decrease in income during social restrictions and export-import